Internalization of Islamic Education Values Through The Practice of Dhikr For Students - Meyniar Albina; Abdul Fattah Nasution (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The processing of the heart, which is essential to the development of the Muslim personality, can only be accomplished through dhikr. This study aims to examine the character-building habit of remembering that students at SMAN 2 Medan follow. It is used by SMAN 2 Medan to mold student character. Researchers combined an analytical descriptive study method with a qualitative approach. Combining observation, interviewing, and documentation studies to gather data Additionally, data analysis uses data display and data reduction methods to draw conclusions. The findings revealed that: (1) Dhikr dahr, Dhikr sir, and Dhikr fi'ly were the forms of Dhikr education that were used; (2) Dhikr's contribution to forming the character of the nation's generation is to ingrain Dhikr firmly into the hearts of generations; (3) The supporting factor for the practice of this Dhikr is the policy of the relevant school. While students' feelings of lethargy are the main barrier, and (4) Dhikr strongly encourages the development of Muslim qualities in students.